2022
DOI: 10.1111/jace.18383
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐silicate‐hydrates/polycarboxylate ether nanocomposites doped by magnesium: Enhanced stability and accelerating effect on cement hydration

Abstract: C‐S‐H/PCE (calcium‐silicate‐hydrates/polycarboxylate ether) nanocomposites have a significant accelerating effect on early hydration and early strength development of cementitious materials. In this study, magnesium ions are doped into C‐S‐H/PCE nanocomposites, and it is found that C‐S‐H/PCE nanocomposites doped by appropriate magnesium ions have much better stability. Besides, the accelerating effects of the modified nanocomposites on early cement hydration also get improved. The doped magnesium ions displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has also been recently reported that C-S-H/PCE nanocomposites incorporating magnesium ions, especially at the Ca/Si ratio of 0.8 and Mg/Si ratio of 0.1, have better stabilities [ 117 ].…”
Section: C-s-h Nucleation Seedsmentioning
confidence: 99%
“…It has also been recently reported that C-S-H/PCE nanocomposites incorporating magnesium ions, especially at the Ca/Si ratio of 0.8 and Mg/Si ratio of 0.1, have better stabilities [ 117 ].…”
Section: C-s-h Nucleation Seedsmentioning
confidence: 99%
“…The size distributions of nano C-S-H is an important factor affecting the early reinforcement effects [31,32]. Theoretically, there is a negative correlation between the size of nano C-S-H and its nucleation effects; therefore, nano C-S-H with smaller size always results in a higher early strength for a cement-based matrix.…”
Section: Introductionmentioning
confidence: 99%